The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.9789/2175-5361.2016.v8i4.4929-4934
|View full text |Cite
|
Sign up to set email alerts
|

Fatores relacionados ao desenvolvimento de úlceras em pacientes com Diabetes Mellitus Factors related to the development of ulcers in patients with Diabetes Mellitus

Abstract: Fatores relacionados ao desenvolvimento de úlceras em pacientes com Diabetes Mellitus ABSTRACTObjective: To identify factors related to the development of ulcers in the lower limbs of insulin-dependent users residing in the city of São José de Mipibu/RN. Method: Quantitative research; we obtained data thought interview followed by static inspection and application of Semmes-Weinstein monofilaments to assess the threshold of plantar tactile sensitivity. The Ethics Committee of the Potiguar University of Natal/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…However, this data differs from that found in the present investigation, since most of the patients evaluated had a time of diagnosis of the disease of less than ten years. Another data identified in this study was that a significant portion of the patients had the foot lesion installed for a period equal to or greater than 30 days, making them more susceptible to serious infections and increasing the healing time (22) .…”
Section: Discussionmentioning
confidence: 86%
“…However, this data differs from that found in the present investigation, since most of the patients evaluated had a time of diagnosis of the disease of less than ten years. Another data identified in this study was that a significant portion of the patients had the foot lesion installed for a period equal to or greater than 30 days, making them more susceptible to serious infections and increasing the healing time (22) .…”
Section: Discussionmentioning
confidence: 86%
“…In this study, it was found that a significant association exists between foot self-care knowledge and level of education. A review by different authors who addressed the subject (12,(19)(20) also identified statistically significant associations between level of education and foot self-care knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…The National Health Survey (Pesquisa Nacional de Saúde-PNS) found a pattern of risk factor for chronic diseases, mainly Systemic Arterial Hypertension (SAH) associated with diabetes 18 . Another study that evaluated the responses of adults in the PNS 2013 points out SAH (65%) as a factor related to the development of ulcers in the lower limbs in people with DM 19 .…”
Section: Discussionmentioning
confidence: 99%